KEBIJAKAN PENETAPAN UPAH MINIMUM DI KABUPATEN DELI SERDANG - Ananda, Syalsa Billa; Yuliana, Yayuk (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Wages are one of the obligations given by the company to workers in return for their work. However, wages are still a problem in the workforce. In fact, the wage setting policy has been stipulated in government laws and regulations. The purpose of this study was to determine the stages of the minimum wage setting policy for workers, what stages were carried out and whether the minimum wage setting policy in Deli Serdang Regency was good. The research method used is descriptive research, the data source used is qualitative data from the results of documentation and quantitative data in the form of secondary data obtained from the Central Statistics Agency of Deli Serdang Regency. From the research results, it is concluded that the determination of the minimum wage in Deli Serdang is influenced by economic and labor conditions, seen from the minimum wage which fluctuates every year due to the influence of increasing economic and labor conditions. The relationship between economic conditions and employment is very close, the workforce exists to support the economy and the district's minimum wage setting policy as a regulation to achieve the welfare of workers' lives.